2008
DOI: 10.1103/physreve.77.036703
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rarefaction on the flow dynamics of a stationary supersonic hot-gas expansion

Abstract: The gas dynamics of a stationary hot-gas jet supersonically expanding into a low pressure environment is studied through numerical simulations. A hybrid coupled continuum-molecular approach is used to model the flow field. Due to the low pressure and high thermodynamic gradients, continuum mechanics results are doubtful, while, because of its excessive time expenses, a full molecular method is not feasible. The results of the hybrid coupled continuum-molecular approach proposed have been successfully validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This can be determined dynamically, e.g. based on the local value of the Knudsen number [28,36,37], or statically, based on some a priori knowledge about the flow characteristics [15,19,35].…”
Section: Introductionmentioning
confidence: 99%
“…This can be determined dynamically, e.g. based on the local value of the Knudsen number [28,36,37], or statically, based on some a priori knowledge about the flow characteristics [15,19,35].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the remote character of the ETP, the effect of electric field forces on the transport of nanoparticles is negligible, and particle transport is dominated by the convective flow and the diffusional processes [1]. In the ETP, the plasma expands in the form of a central beam, which is surrounded by background regions, or recirculation cells [26][27][28]. The flow in the central beam draws a linear trajectory for the growth of nanoparticles under convective transport, particularly with a beam residence time of τ beam ∼ 10 ms leading to growth of small Si-NCs in the size range 2-10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Other experiments on the invasion of supersonic rarefied plasma jets by background gas , concluded that part of the molecules in the zone of silence come indeed from the background gas, crossing the barrel shock wave. Numerical simulations of those jets yielded values of the local Knudsen number (eq ) greater than 0.1 in an extensive region of the zone of silence. With such large Knudsen numbers it may be expected that a significant fraction of the molecules that cross the barrel shock could reach the jet axis.…”
Section: Resultsmentioning
confidence: 99%